Consideration of the oxide particle–dislocation interaction in 9Cr-ODS steel. Issue 13 (3rd May 2017) - Ijiri, Yuta; Oono, N.; Ukai, S.; Yu, Hao; Ohtsuka, S.; Abe, Y.; Matsukawa, Y.
Abstract: The interaction between oxide particles and dislocations in a 9Cr-ODS ferritic steel is investigated by both static and in situ TEM observation under dynamic straining conditions and room temperature. The measured obstacle strength ( ) of the oxide particles was no greater than 0.80 and the average was 0.63. The dislocation loops around some coarsened particles were also observed. The calculated obstacle strength by a stress formula of the Orowan interaction is nearly equaled to the average experimental value. Not only cross-slip system but also the Orowan interaction should be considered as the main interaction mechanism between oxide particles and dislocation in 9CrODS ferritic steel.